Expression of collagen type III and type IV in breast cancer - Goździalska, Anna; Gawędzka, Anna; Drąg, Jagoda; Knapik-Czajka, Małgorzata; Siekanowicz, Anna; Kużdżał, Adrian; Jaśkiewicz, Jerzy (European Journal of Clinical and Experimental Medicine, 2010)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Introduction: Breast cancer is the most common cause of cancer death in women in Poland and it is the second most frequent cancer in women worldwide. The structure of both healthy as well as tumor breast tissue is maintained by extracellular matrix components including collagens. The rate of collagens degradation depends on matrix metalloproteinases (MMPs) activities. In non tumor tissue the turnover rate of extracellular matrix is the crucial factor in preserving the proper function of the breast tissue, while in cancer it reflects the dynamics of tumor cell infiltration. The main objective of our study was to determine the expression of collagen type III and type IV proteins in breast tissue obtained from women with diagnosed breast cancer. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Materials and Methods: From each patient two specimens of breast tissue were taken during mastectomy, one from the tumor center and the second from the bordering healthy tissue (control group). Expression of both types of collagen proteins was evaluated by Western blot technique with chemiluminescence detection. The results obtained for collagen III and IV of the tumor and nontumor tissue, were expressed as a mean value ± SD of collagen expression. D’Agostino test for normality of distribution was assessed. The parametric test (t-Student’s test) and Wilcoxon pair sequence were used to verify the results. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Results: The results of this study demonstrated the expression of type III and type IV collagen proteins in both tumor and non tumor breast tissue. The expression of different types of collagen according to age was demonstrated. Patients in the group up to 55 years of age found a higher expression of type IV collagen in the nontumor tissues, while in the group above 55 years of age the expression of collagen IV was higher in the tumor. Statistically significant differences in the expression of collagen type IV between tumor and non tumor tissue, in only the group over 55 years of age were found. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Conclusions: The different expression of collagen proteins in tumor and nontumor tissues may be one of the markers used in breast cancer diagnostics.